Balsas lipídicas são necessárias para a translocação do receptor lipídicas são necessárias para a translocação do receptor do fator de crescimento epidermal para o núcleo - Ana Carolina De Angelis Campos (2010)
The epidermal growth factor receptor (EGFR) regulates cellular process of ligands such as EGF and transforming growth factor alpha (TGF-α). Upon activation EGFR initiates signaling cascades that can result in cell proliferation, differentiation, migration and survival. Recently it was shown that EGFR can be translocated to the nucleus after ligand stimulation, where it acts as a transcription factor and signal transducer. Abnormal expression and/or mutations of EGFR are implicated in the progression of ephitelial-derived solid tumors and its block by monoclonal antibodies (mAbs) is an important target for cancer therapy. However, recent data point that nuclear EGFR (nEGFR) is involved in acquired resistence to mAbs and this localization of the receptor represent a major prognostic value for patients with some kind of tumors. Regardless of the nEGFR importance has been demonstrated, the mechanisms by which this receptor is translocated to the nucleus is not clear. Thus, the present study aimed to identify the endocytic pathway that mediates the nuclear translocation of EGFR. SKHep-1 cells, a liver cell line, was used. To determine differences in the subcellular distribution of EGFR after EGF stimulation, nuclear and non-nuclear cell fractions were analyzed by immunoblot and by real time imaging and confocal immunofluorescence. Small interference RNA was used to knockdown clathrin and caveolin. Intracellular trafficking of EGF was examined by time lapse confocal imaging of EGF labeled with Alexa 488 or 555. Cell fractionation studies showed that EGFR was detectable in the nucleus after EGF stimulation, with a peak in nuclear receptor after 10 min. Movement of EGFR to the nucleus was confirmed by confocal immunofluorescence. Alexalabeled EGF co-localized with EGFR, and internalization of labeled EGF was blocked by treatment with caveolin siRNA. EGF internalization also was impaired by the dynamin dominant negative mutant K44A. Cell fractionations furthermore showed that appearance of EGFR in the nucleus could be blocked by either Methyl-beta-Cyclodextrin (MβCD) to disrupt lipid rafts or treatment with caveolin siRNA. However, knockdown of clathrin with siRNA did not block nuclear accumulation of EGFR.